2018
DOI: 10.1113/jp276618
|View full text |Cite
|
Sign up to set email alerts
|

Neural memory of the genioglossus muscle during sleep is stage‐dependent in healthy subjects and obstructive sleep apnoea patients

Abstract: Several studies have shown that obstructive sleep apnoea (OSA) improves during slow wave sleep (SWS) for reasons that remain unclear. Recent studies have identified forms of neural memory such as short-term potentiation or after-discharge that can occur in response to upper airway obstruction. Neural memory may play a role in the development of stable breathing during SWS by increasing upper airway muscles activity in this sleep stage. We hypothesize that the after-discharge of the genioglossus muscle followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Moreover, the drugs tested to date were unable to increase the arousal threshold by more than 20–30% (see below for a detailed description). Ideally, a drug that mimics the effects of slow wave sleep (a state in which the arousal threshold is elevated) would be ideal for reducing OSA severity, given that this is a relatively protected stage of sleep in regards to OSA [111,112,113,114].…”
Section: Arousal Thresholdmentioning
confidence: 99%
“…Moreover, the drugs tested to date were unable to increase the arousal threshold by more than 20–30% (see below for a detailed description). Ideally, a drug that mimics the effects of slow wave sleep (a state in which the arousal threshold is elevated) would be ideal for reducing OSA severity, given that this is a relatively protected stage of sleep in regards to OSA [111,112,113,114].…”
Section: Arousal Thresholdmentioning
confidence: 99%
“…After-discharge in the genioglossus muscle has been recently proposed to be a protective factor for OSA, as it prevents periods of low genioglossus muscle activity following a period of increased respiratory drive, such as at the termination of respiratory events, after the arousals. Although multiunit genioglossus after-discharge (inspiratory and expiratory) was not found to differ between patients with OSA and healthy individuals following reversal of upper airway obstruction [42], enhancement of after discharge may still have a role in OSA treatment. Our group in Boston has recently shown that greater and longer after discharge is associated with slow wave sleep [42], a protected sleep state in which OSA patients experience less obstructive events and more stable breathing on average.…”
Section: Key Pointsmentioning
confidence: 85%
“…Although multiunit genioglossus after-discharge (inspiratory and expiratory) was not found to differ between patients with OSA and healthy individuals following reversal of upper airway obstruction [42], enhancement of after discharge may still have a role in OSA treatment. Our group in Boston has recently shown that greater and longer after discharge is associated with slow wave sleep [42], a protected sleep state in which OSA patients experience less obstructive events and more stable breathing on average. Other characteristics of deep sleep that may help upper airway muscle recruitment and reduced respiratory events are the higher arousal threshold and ventilatory drive measured during this stage.…”
Section: Upper Airway Muscles Pathophysiology In Obstructive Sleep Ap...mentioning
confidence: 85%
“…In an article in this issue of The Journal of Physiology , Taranto‐Montemurro et al . () explore the possibility that the improved UA stability in SWS may result from a more potent AD in this stage. They indeed found this to be true both in healthy controls and in OSA patients; the duration of AD increased as the same subjects entered SWS.…”
mentioning
confidence: 99%
“…The exact mechanism for this was not known although it was suspected that higher arousal threshold in SWS contributed by delaying arousal and allowing the normal compensatory mechanisms to progress to the required level. In an article in this issue of The Journal of Physiology, Taranto-Montemurro et al (2018) explore the possibility that the improved UA stability in SWS may result from a more potent AD in this stage. They indeed found this to be true both in healthy controls and in OSA patients; the duration of AD increased as the same subjects entered SWS.…”
mentioning
confidence: 99%